1992
DOI: 10.1017/s0022112092004415
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory instability of cellular flames propagating in tubes

Abstract: In this paper, we study the vibratory instability of a cellular flame, propagating downwards in a tube, which results from the coupling between the longitudinal acoustic modes of the tube and the modification of the cellular flame structure by the acceleration of the acoustic field. We assume that the wrinkling of the flame is of small amplitude a0, which is the case when the flame burning velocity is just above the critical velocity characterizing the Darrieus–Landau instability threshold. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 8 publications
7
54
1
Order By: Relevance
“…Then, the increasing velocity gradients induce change in the flame surface area, which is in phase with pressure fluctuation, and the primary acoustic sound is generated. Finally, the variation in the flame surface area caused by the acoustic velocity field forces the amplification of the primary acoustic sound and leads to the stabilization of D-L instability [1,2,11]. Their calculation indicates that the maximum growth rate takes place in the lower half of the tube, which is in good agreement with Searby's experimental observations [1].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Then, the increasing velocity gradients induce change in the flame surface area, which is in phase with pressure fluctuation, and the primary acoustic sound is generated. Finally, the variation in the flame surface area caused by the acoustic velocity field forces the amplification of the primary acoustic sound and leads to the stabilization of D-L instability [1,2,11]. Their calculation indicates that the maximum growth rate takes place in the lower half of the tube, which is in good agreement with Searby's experimental observations [1].…”
Section: Introductionsupporting
confidence: 66%
“…An approach toward resolving this issue has generally been to consider the Rayleigh criterion [5]: an acoustic wave will be amplified if a time integral of the product of pressure and heat release fluctuations is positive over a pressure cycle. Considering this criterion, many previous researchers [6][7][8][9][10][11][12] have proposed various mechanisms on primary acoustic instability. We can classify them into two large groups depending whether they are related to coupling of the acoustic Initially, Dunlap [7] theoretically showed that the effect of the pressure and adiabatic temperature of an incoming acoustic wave modulates local heat release rates of a flame with the correct phase relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They formulated and solved the stability problem of a flame subjected to an externally prescribed acoustic pressure, and showed that as the acoustic acceleration exceeds a threshold, it induces a violent subharmonic parametric instability. Pelce & Rochwerger (1992) analyzed the acoustic instability of a (slightly) curved stationary flame, and showed that the unsteady heat release due to the flame surface-area change drives exponential growth of acoustic modes. The back effect of the latter on the flame was however not considered.…”
Section: Premixed Combustion and Instabilitymentioning
confidence: 99%
“…A general asymptotic theory was presented by Wu, Wang, Moin & Peters (2003) (referred to as WWMP hereafter) to describe the acoustic-flow-flame coupling in the 'corrugated flamelet' regime. Using this general formulation, they provide a unified description of the flame-acoustic coupling mechanisms of Clavin et al (1990) and Pelce & Rochwerger (1992).…”
Section: Premixed Combustion and Instabilitymentioning
confidence: 99%